GRB 181110A: Constraining the Jet Structure, Circumburst Medium and the Initial Lorentz Factor - Song Han; Xinyu Li; Luyao Jiang; Zhiping Jin; Haoning He; Yuanzhu Wang; Daming Wei (Universe, 2022)
The afterglow data of gamma ray bursts (GRBs) can be used to constrain the physical properties of the fireball (e.g., the jet structure and opening angle) and the circumburst medium. With the peak time of the early afterglow light curve being taken as the deceleration time, one can estimate the initial Lorentz factor of the fireball. In this work, we perform a comprehensive analysis on the prompt emission and the afterglow data of GRB 181110A, where a clear peak is detected by Swift UVOT and XRT in optical to X-ray bands. Prompt emission spectral analysis shows that the spectrum of GRB 181110A is soft, and both hard-to-soft and intensity-tracking spectral evolution are found. By fitting the afterglow light curve and building spectral energy distribution, we find that the standard external forward shock model with a constant circumburst medium is favored, and the jet structure of GRB 181110A tends to be uniform rather than structured. With the peak time of early afterglow emission, we estimate the initial fireball Lorentz factor of GRB 181110A to be <semantics>Γ0=<msubsup>169−40+92</msubsup></semantics>. We also compare GRB 181110A with other typical long GRBs in a statistical context.